Characterization of NAC transcription factor family of Tectona grandis involved in secondary cell wall deposition and stress response - Hurtado, Fernando Manuel Matias (2020)
NAC proteins are one of the largest families of plant-specific transcription factors (TFs). They regulate diverse biological processes, including secondary cell wall formation (SCW). SCW is the main component of wood and source of raw material in forestry industry, Tectona grandis (teak) specie is recognized for presenting one of the most valuable woods in the world due to its extraordinary qualities of color, density and durability. Studies of teak genomics and transcriptomics were recently unveiled, producing information that allowed to identify teak NAC transcription factors and to analyse their evolution and expression profile during wood formation. It was identified 130 NAC proteins that were coded by 107 gene loci. These proteins were classified into 23 clades of the NAC family, together with Populus, Eucalyptus, and Arabidopsis. Data on transcription expression revealed specific temporal and spatial expression patterns for the majority of teak NAC genes. The qRT-PCR indicated expression of VASCULAR NAC DOMAIN proteins involved in SCW formation in xylem vessels of 16-year-old juvenile trees. In addition, it was characterized by heterologous expression, the novel salt stress-responsive TgNAC01 gene. Three independent transgenic tobacco lines overexpressing TgNAC01 were generated. It was demonstrated that the TgNAC01 protein is localized only in the nucleus. Analyses of TgNAC01 relative expression, stem length and chlorophyll content were evaluated in two months old transgenic plants growing in greenhouse. Tobacco plants overexpressing TgNAC01 showed higher stem length, an increase in leaf senescence, and tolerance to 300 mM of NaCl when compared to wild type (WT) plants. Water potential, gas exchange and chlorophyll fluorescence were used to determine the salt stress tolerance. In this research, it was demonstrated that TgNAC01 transcription factor acts as a positive regulator in xylem development and as a transcriptional activator mediated by salt stress and leaf senescence. These results open a way to further understanding of NAC transcription factor genes in T. grandis wood formation and stress tolerance, potentially being useful for future studies aiming to improve productivity and wood quality using biotechnological approaches.